RANKL-dependent and RANKL-independent mechanisms of macrophage-osteoclast differentiation in breast cancer. - Lau, Y; Danks, L; Sun, S; Fox, S; Sabokbar, A; Harris, A; Athanasou, N (2007)
The cellular and humoral mechanisms accounting for tumour osteolysis in metastatic breast cancer are uncertain. Osteoclasts, the specialised multinucleated cells responsible for tumour osteolysis, are derived from monocyte/macrophage precursors. Breast cancer-derived tumour-associated macrophages (TAMs) are capable of osteoclast differentiation but the cellular and humoral mechanisms controlling this activity are uncertain. In this study, TAMs were isolated from primary breast cancers and cultured in the presence and absence of cytokines/growth factors influencing osteoclastogenesis. Extensive TAM-osteoclast differentiation occurred only in the presence of RANKL and M-CSF; this process was inhibited by OPG and RANK:Fc, decoy receptors for RANKL. Breast cancer-derived fibroblasts and human bone stromal cells expressed mRNA for RANKL, OPG and TRAIL, and co-culture of these fibroblasts with human monocytes stimulated osteoclast formation by a RANKL-dependent mechanism. Osteoclast formation and lacunar resorption also occurred by a RANKL-independent mechanism when the conditioned medium from breast cancer cells, MDA-MB-231 and MCF-7, was added (with M-CSF) to monocyte cultures. Our findings indicate that TAMs in breast cancer are capable of osteoclast differentiation and that breast cancer-derived fibroblasts and breast cancer cells contribute to this process by producing soluble factors that influence osteoclast formation by RANKL-dependent and RANKL-independent mechanisms respectively.